Circadian Neuropeptide-Expressing Clock Neurons as Regulators of Long-Term Memory: Molecular and Cellular Perspectives - Inami, Show; Sato, Tomohito; Sakai, Takaomi (Frontiers in Molecular Neuroscience, 2022)
The neuropeptide Pigment-dispersing factor (Pdf) is critically involved in the regulation of circadian rhythms in various insects. The function of Pdf in circadian rhythms has been best studied in the fruitfly Drosophila melanogaster. Drosophila Pdf is produced in a small subset of circadian clock neurons in the adult brain and functions as a circadian output signal. Recently, however, Pdf has been shown to play important roles not only in regulating circadian rhythms but also in innate and learned behaviors in Drosophila. In this mini-review, we focus on the current findings that Pdf signaling and Pdf-producing neurons are essential for consolidating and maintaining long-term memory induced by courtship conditioning in Drosophila and discuss the mechanisms of courtship memory processing through Pdf-producing neurons.